Leadership and personality attributes of Tan Sri Muhyiddin Yassin - Ssemuddu, Imran; Syed Abdullah Idid, Syed Arabi; Ahmad, Zeti Azreen (2021)
The current study is on the leadership qualities of a high profile Malaysian leader. Specifically, the objectives of this study focus on the leadership qualities and the personal qualities of Tan Sri Muhyiddin Yassin, who became the 8th Prime Minister of Malaysia in March 2020, heading the Perikatan Nasional Government.Various studies have identified the different qualities of leadership which include confidence, visionary, balanced, sociability, integrity, persistence, and responsibility. Others include family values, religious, Amanah, courageous, tolerant, fair, accountable, helpful, good communication skills. Leaders are charismatic and are role models who influence social values in affecting communities and beliefs. Leaders make a difference, whether in terms of affecting preferences or beliefs of followers. Not many studies have been done in Malaysia on leadership qualities to add to the findings. The study of leadership can take many forms but the present study approaches it qualitatively. A survey was conducted in July 2020 using a questionnaire as the research instrument for data collection. The nationwide face-to face study asked a total of 822 respondents to give the personal and leadership attributes of Muhyiddin Yassin. All the answers given were recorded and then tabulated as positive and negative attributes. The findings of the study indicated Tan Sri Muhyiddin Yassin exhibited leadership and personality qualities of fairness, firmness, and ability to deal with COVID-19 pandemic. Regarding his personality, respondents thought him as people-oriented, and has a good personality. The negative attributes were not being fair, and helpful. The attributes of leadership change given the circumstances of time. This study will invite discussion on the qualitative approach of conducting research on leadership qualities and how factors influenced people’s perception of a leader.